Effect of Textured Vegetable Protein Type on Quality of Plant-Based Meat Product - Tunnarut, Duenchay; Atchareeya Nopwinyuwong,; Tanakamolpradit, Tanita (Journal of Food Technology, Siam University, 2022)
Plant-based meat products have emerged as one of the fast-growing industries, and they are made from a variety of artificial meats or textured vegetable proteins, with different characteristics. The effect of textured vegetable protein types (soy protein A, soy protein B, pea protein A, pea protein B and wheat protein) on texture profile analysis, protein content, moisture content, color and sensory liking scores of plant-based meat products was investigated in this study. Plant-based meat products prepared from soy protein B showed higher hardness and chewiness than other proteins (p<0.05). The product has a high protein content about 15.7% and a moisture content of 60-70%. The liking scores for appearance, nutty flavor/wheat flavor, taste, texture and overall liking were higher than other proteins. With the exception of the meat color liking score, plant-based meat products prepared from pea protein A received the second-highest score (p>0.05). In addition, 75% of consumers accept plant-based meat products prepared from soy protein B. This research shows that it can be further developed into plant-based meat products.